Combined effect of reticular stimulation and physostigmine on hippocampal theta activity - Hlavička, Pavel; Radil, Tomáš (Acta Neurobiologiae Experimentalis, 1982)
The effect of electrical stimulation of the mesencephalic reticular formation and of physostigmine on hippocampal theta activity was combined in rats with implanted electrodes. The effect was not additive. The threshold for evoking motor activity by means of reticular stimulation decreased after physostigmine administration.
Keywords: Mesencephalon; elektrická stimulace; retikulární formace; fysostigmin; krysa rodu Rattus; Hippocampus; Animals; Electric Stimulation; Rats; Reticular Formation; Physostigmine; theta rytmus EEG; Theta Rhythm; Nerve Net; zvířata; nervová síť; hipokampus; mezencefalon